Penerapan Sanksi Disiplin Terhadap Anggota Polri Yang Melakukan Perkawinan Siri - Riza Chatias Pratama; Dinard Fhathird (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Siri marriage is a marriage between a man and woman, without permission and without the prior wife's knowledge. In Indonesia, marriage itself is a crime because it has been regulated in the law. Indonesian Criminal Code provides sentence to perpetrators of marital threats threatening a maximum of 5 years in prison. In practice, Siri marriages still occur, and are also carried out by members of the National Police. This study uses empirical normative research methods that use data in the form of primary legal materials and secondary legal materials. Data collection is done by field research (field research and library research), then the data is analyzed quantitatively. The results showed that the factors causing the occurrence of marital marriages were psychological factors, disharmony in the household, lack of legal awareness of regulations and the existence of conflicting legal procedures or discipline / discipline. The application of disciplinary sanctions is carried out after the District Court's verdict, then the Polri Professional Code of Ethics session is held. Obstacles in its remedies are due to interventions of the police independence in handling cases or human resource development and lack of complaints of negative behavior.